Modulation of spontaneous breathing via limbic/paralimbic-bulbar circuitry: An event related fMRI study - Evans, Karleyton C. (2009)
It is well established that pacemaker neurons in the brainstem provide automatic control of breathing for metabolic homeostasis and survival. During waking spontaneous breathing, cognitive and emotional demands can modulate the intrinsic brainstem respiratory rhythm. However the neural circuitry mediating this modulation is unknown. Studies of supra-pontine influences on the control of breathing have implicated limbic/paralimbic-bulbar circuitry, but these studies have been limited to either invasive surgical electrophysiological methods or neuroimaging during substantial respiratory provocation. Here we probed the limbic/paralimbic-bulbar circuitry for respiratory related neural activity during unlabored spontaneous breathing at rest as well as during a challenging cognitive task (sustained random number generation). Functional magnetic resonance imaging (fMRI) with simultaneous physiological monitoring (heart rate, respiratory rate, tidal volume, end-tidal CO(2)) was acquired in 14 healthy subjects during each condition. The cognitive task produced expected increases in breathing rate, while end-tidal CO(2) and heart rate did not significantly differ between conditions. The respiratory cycle served as the input function for breath-by-breath, event-related, voxel-wise, random-effects image analyses in SPM5. Main effects analyses (cognitive task + rest) demonstrated the first evidence of coordinated neural activity associated with spontaneous breathing within the medulla, pons, midbrain, amygdala, anterior cingulate and anterior insular cortices. Between-condition paired t-tests (cognitive task > rest) demonstrated modulation within this network localized to the dorsal anterior cingulate and pontine raphe magnus nucleus. We propose that the identified limbic/paralimbic-bulbar circuitry plays a significant role in cognitive and emotional modulation of spontaneous breathing.